The resource availability hypothesis (RAH) and cross-cultural patterns: which one explains West African Cochlospermum species' uses in Benin? - Gnimansou Abraham Favi; Gbèwonmèdéa Hospice Dassou; Donald Djidohokpin; Jéronime Marie-Ange Sènamie Ouachinou; Chabi Ghyslain Kpétikou; Eutiche Gbedolo; Alain Anagonou; Noelia Hidalgo-Triana; Aristide Cossi Adomou (BMC, 2022)
Abstract Background Cochlospermum tinctorium and C. planchonii are two wide edible plants of sub-Saharan countries, e.g., Benin, widely used as food, medicine, dye, handicraft, etc. Unfortunately, the uncontrolled harvest of their rootstocks exposes them to local extension risk. To enhance knowledge on the determinants of their uses in Benin, this study aimed to (i) assess the use forms, use values, abundance and perceived spatiotemporal dynamics, (ii) determine how does local abundance or cultural patterns affect the use of Cochlospermum species, and (iii) assess local harvesting modes and conservation management practices. Methods In total, 756 Dialog Partners through 27 ethnic groups were questioned countrywide using semi-structured interviews. Questions refer to local taxonomy, specific uses, organs sought, harvesting modes and local conservation strategies; afterward, local abundance of each species was assessed. Ethnobotanical indicators were analyzed through citation frequencies to obtain quantitative data. Comparison tests and statistical analyses were performed using R program. Results C. tinctorium and C. planchonii are locally well known and involved into 83 specific uses, grouped into ten categories of which medicinal use was the main. The use values of C. planchonii (0.10 ± 0.19) and C. tinctorium (0.23 ± 0.20) varied significantly between the ethnic groups, and only C. tinctorium showed index of commercially value above 75% for some ethnic groups. The current abundance, about 84 and 97 tufts.ha−1, respectively, for C. planchonii and C. tinctorium was perceived with a decline of 81.09% (C. tinctorium) and 73.7% (C. planchonii) of informants. Moreover, the Spearman's correlation and Kruskal-Wallis tests performed revealed that the use values of C. tinctorium and C. planchonii were significantly correlated on the one hand with their local abundance and on the other hand with the investigated ethnic groups. About 42.3% of women produced the powder as principal activity, while more than 57% produced it mainly at the end of farm work. However, the conservation management was practiced by very few informants and consisted of partial harvesting of rootstocks (41.8%, only in southern Benin), and fallowing of harvesting areas (3.97%, only in northern Benin). Conclusion Facing the declining abundance and increasing market demand for rootstock powder of Cochlospermum species, existing local conservation strategies should be promoted and the domestication process should be initiated for sustainable management of these important wild edible plants before these important resources disappear completely in the wild.